(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Architects and designers have a critical role in promoting Life Cycle Assessment (LCA), a scientific methodology for evaluating the environmental impacts of buildings that can help decarbonise the built environment and minimise other negative effects. This paper presents the results of an international survey conducted among design professionals as part of the IEA Annex 72 project about assessing life cycle related environmental impacts caused by buildings. Twenty-three countries were participating in the survey altogether, but in this paper, only the specific situation in two Central European countries, Hungary and Czechia, are presented. The questionnaire explored the designers’ understanding of environmental problems and LCA methodology, the drivers and barriers of environmental assessment and the future perspectives. The results show that many architects and designers are concerned about environmental problems and the built environment’s contribution but have a limited understanding of the applicable scientific methods. A full LCA is seldomly applied as neither regulations nor clients demand it, and only the operational energy is mandatorily assessed. Further improvements in data quality and assessment tools and regulatory and other drivers are needed to increase the use of LCA in the construction sector.